Nanomaterial-based cancer immunotherapy: enhancing treatment strategies - Tian, Mengxiang; Liu, Xionglin; Pei, Haiping (Frontiers in Chemistry, 2024)
Cancer immunotherapy has emerged as a pivotal approach for treating various types of cancer, incorporating strategies such as chimeric antigen receptor T-cell (CAR-T) therapy, immune checkpoint blockade therapy, neoantigen peptides, mRNA vaccines, and small molecule modulators. However, the clinical efficacy of these therapies is frequently constrained by significant adverse effects and limited therapeutic outcomes. In recent years, the integration of nanotechnology into cancer immunotherapy has gained considerable attention, showcasing notable advantages in drug delivery, targeted accumulation, controlled release, and localized administration. This review focuses on nanomaterial-based immunotherapeutic strategies, particularly the development and application of nanocarriers such as liposomes, lipid nanoparticles, polymeric nanoparticles, and self-assembling scaffolds. We examine how these strategies can enhance the efficacy of cancer immunotherapy while minimizing adverse effects and analyze their potential for clinical translation.